Cleaning up nitrogen pollution may reduce future carbon sinks. (January 2018) - Gu, Baojing; Ju, Xiaotang; Wu, Yiyun; Erisman, Jan Willem; Bleeker, Albert; Reis, Stefan; Sutton, Mark A.; Lam, Shu Kee; Smith, Pete; Oenema, Oene; Smith, Rognvald I.; Lu, Xuehe; et al.
Highlights: Ratio of anthropogenic CO2 and N emissions to atmosphere monotonously increases with economic growth. Anthropogenic CO2 and N emissions to atmosphere both show an asymmetric para-curve with economic growth. Inflection points of CO2 and N emissions are found at around $15, 000 GDP per capita. There will be relatively more anthropogenic CO2 emission but less N deposition with economic growth. Efforts to manage CO2 and N emissions comprehensively to maintain a balance are critical. Abstract: Biosphere carbon sinks are crucial for reducing atmospheric carbon dioxide (CO2 ) concentration to mitigate global warming, but are substantially affected by the input of reactive nitrogen (Nr ). Although the effects of anthropogenic CO2 emission and nitrogen deposition (indicated by Nr emission to atmosphere) on carbon sink have been studied, it is unclear how their ratio (C/N) changes with economic development and how such change alters biosphere carbon sinks. Here, by compiling datasets for 132 countries we find that the C/N ratio continued to increase despite anthropogenic CO2 and Nr emissions to atmosphere both showing an asymmetric para-curve with economic growth. The inflection points of CO2 and Nr emissions are found at around $15, 000 gross domestic product per capita worldwide. Economic growth promotes the use of Nr and energy, while at the same time increases their use efficiencies, together resulting in occurrences of inflection points of CO2 and Nr emissions. Nr emissions increase slower but decrease faster than that of CO2 emissions before and after the inflection point, respectively. It implies that there will be relatively more anthropogenic CO2 emission but less N deposition with economic growth. This may limit biosphere carbon sink because of relative shortage of Nr. This finding should be integrated/included in global climate change modelling. Efforts, such as matching N deposition with carbon sequestration on regional scale, to manage CO2 and Nr emissions comprehensively to maintain a balance are critical.